The Role of Parent-Child Communication in Preventing Adolescent Mental Health Issues: A Phenomenological Study - Denta Rahma Fitriyani (P3M STAI Kuningan, 2025)
Background: Adolescent mental health issues such as depression, anxiety, and behavioral problems have reached critical levels globally, emphasizing the need for effective prevention strategies.Objective: This review aims to examine the preventive role of parent-child communication in adolescent mental health, particularly from a family counseling perspective. It synthesizes recent empirical evidence (2021-2025) to understand how positive communication patterns influence mental health outcomes in adolescents.Method: The review draws from 45 contemporary studies, examining the role of parent-child communication in preventing adolescent psychopathology. It includes research across diverse cultural contexts, such as China, Uganda, and Native American communities, and considers both face-to-face and digital communication. Specific counseling interventions focusing on communication enhancement were also explored, with a particular focus on emotion-focused approaches, mindful parenting, and attachment-based strategies.Findings and Implications: Positive communication patterns, characterized by warmth, emotional validation, active listening, and conflict management, were found to significantly reduce risks of depression, anxiety, and behavioral problems, while promoting life satisfaction, coping abilities, and resilience. Parent-child communication also plays a crucial role in emotion regulation, coping strategies, and self-compassion development. The COVID-19 pandemic highlighted the importance of communication, as it buffered against pandemic-related psychological distress and facilitated posttraumatic growth. While communication expressions vary across cultures, emotional attunement and respectful dialogue are universal protective factors.Conclusion: The rise of digital communication introduces challenges but highlights that quality communication across both face-to-face and online channels is essential.